Wild sky - Kinahan, Deirdre (Nick Hern Books, 2022)
Wild Sky is a story of interlocking lives: of the politicised Josie Dunne, and of Tom Farrell, who is driven only by his love for her. As the Rising plays out, there are unforeseen consequences for everyone involved
10.5040/9781784607012.00000003
Keywords: Irish Civil War; National identity; Plays; Politics